Capturing cultural differences between UK and Malaysian drivers to inform the design of in-vehicle navigation systems - Large, David R.; Burnett, Gary; Mohd-Hasni, Yasmin (Society of Automotive Engineering of Japan, 2017)
Attending to cultural diversity is important for products and technology intended for global placement, such as automobiles, yet many products (and associated interfaces) lack genuine cultural differentiation. For example, in-vehicle navigation systems are typically identical in form and function across world markets, differing only in the local language and map database. To capture and explore culturally-salient design factors, we utilised a scenario-based design methodology, involving 6 experienced drivers from the UK and Malaysia. Participants were asked to portray their ideal navigation system interface designs – by drawing pictograms and devising accompanying spoken messages – to direct drivers along 3 prescribed routes in the UK, Malaysia and Japan. Routes were presented using video and paper maps, with the order of presentation counterbalanced between groups; participants were not told in advance from which country each route was derived. Proposed designs highlight differences at a country level, which are consequently interpreted from a cultural perspective. For example, Malaysian drivers included a higher density of navigational elements in their designs, particularly in their home environment, compared to UK drivers. Malaysian drivers also created more incremental designs, particularly on the approach to a manoeuvre, suggesting a desire for greater navigational support at this point in the journey. Landmarks were consistently incorporated in designs, but differences were noted in cultural salience. Additionally, the phrasing of instructions (e.g. “go straight on”), nomenclature for road elements (e.g. ‘roundabout’) and distance declaration conventions (e.g. units) differed at a country level. The findings can be used to inform the design of culturally-attuned in-vehicle navigation systems.